Administering Boiled Water From Soursop Leaves To Reduce Blood Pressure In Hypertensive Sufferers At Kampung Delima Health Center, Rejang Lebong District, Bengkulu Province - Pratiwi, Intan; Rustandi, Handi; Yohandi Putra, Adytia; Sulaika, Belkis; Ersanly, Naomi; Kristifani, Nofela (Jurnal Pengabdian Mandiri, 2024)
Elderly (elderly) is someone aged 60 years and over. As a person gets older, a person's health condition can decline, making him susceptible to various kinds of diseases. This puts elderly people at risk of developing degenerative diseases, namely health conditions that occur due to the deterioration of a tissue or organ over time. The aging process in the elderly will result in physical, mental, social, economic and physiological changes. One of the changes that occurs is changes in the structure of large veins which can result in hypertension (Kristiawan and Adiputra, 2022). Health problems in the elderly begin with the deterioration of body cells, decreased function and endurance, and increased risk factors for disease. A problem often experienced by elderly people is hypertension (Indonesian Ministry of Health, 2021). Soursop leaves (Annona muricata Linn) contain monotetrahydrofuran acetogenin, including anomurisin A and B, gigantetrosin A, annonasin 10 one, muricotasin A and B, annonacin, and goniothalamicin and potassium ions. The benefits of these compounds are for the treatment of various diseases. Other compounds contained in soursop leaves are calcium, phosphorus, carbohydrates, vitamin A, vitamin B, vitamin C, tannins, phytosterols, calcium oxalate and alkaloids. Soursop leaves have anti-oxidants which can ward off free radicals and can also elasticize and stretch blood vessels and lower blood pressure (Yano & Keswara, 2021) This community service has been carried out from July 8 2024 to July 21 2024. Evaluation of the activity is based on analysis report data regarding the effect of soursop leaf boiled water on reducing blood pressure with cardiovascular system disorders: hypertension. Conducted using an experimental method and the number of respondents was 10 people, blood pressure decreased slowly and it was proven that giving soursop leaf decoction could reduce high blood pressure in hypertension sufferers. It is hoped that the conclusion of this report can help science in the health sector in carrying out complementary therapeutic measures for hypertensive patients in reducing high blood pressure in elderly people with hypertension.